Study on the adsorption effect and mechanism of biochar from forest surface fuels on heavy metals - Weilong Zhang; Lixuan Wang; Ruijie Zhang; Dongming Ye; Man Zhang; Fengjun Zhao; Guang Yang (Biomass and Bioenergy, 2027)

Biological fire prevention through fungal degradation: Armillaria mellea alters combustibility of surface fuels in typical China Three-North forests - Furui Jian; Lixuan Wang; Dongming Ye; Guang Yang; Fengjun Zhao; Lin Zhang (Biomass and Bioenergy, 2026)

Effects of microbial-derived artificial humic acid on soil organic carbon stability and microbial community fractions under straw return conditions - Jiaxun Liang; Huaiyuan Teng; Le Liu; Fengjun Yang; Liqin Zhao; Bowen Fan; Jingyi Lan (Applied Soil Ecology, 2026)

Effects of taurine on microbiota composition, metabolic profiles, immune capacity, and survival of Manila Clam (Ruditapes philippinarum) larvae - Yang Liu; Kai Liao; Yang Zhang; Qi Hu; Xiaoxue He; Fengjun Xie; Lin Zhang; Zhongming Huo; Jilin Xu (Aquaculture, 2026)

Methacryloxyethyl sulfobetaine (SBMA) based hydrogel with functional enhancement by acrylamide, glycerol, and thymol for strawberry preservation - Zhichao Yang; Xiaohong Guo; Ziqiang Qin; Fengjun Guo; Di Wu; Bangdi Liu; Kunsong Chen (Food Chemistry, 2026)

The Effect of Humic Acid From Different Raw Materials on Soil Physical and Chemical Properties and Tomato Seedling Growth - Lanjing Long; Liqin Zhao; Xiangjun Chen; Zhicheng Liu; Xue Chen; Bowen Fan; Fengjun Yang (Journal of Soil Science and Plant Nutrition, 2026)

Rapamycin enhances rice resistance to Rhizoctonia solani by reconstructing endophytic microhabitat and ROS homeostasis - Siyu Guo; Jingjing Peng; Changyu Zhu; Bowen Fan; Qin Yao; Fengjun Yang; Changjiang Zhao (Physiological and Molecular Plant Pathology, 2026)

Monitoring surface deformation caused by fluvial-aeolian interaction and its contribution to aeolian process in a small watershed of the Gonghe Basin, northeastern Tibetan Plateau - Na Gao; Guangyin Hu; Linhai Yang; Jingjing Hu; Haokun Mo; Jie Gao; Fengjun Xiao; Zhibao Dong (CATENA, 2026)

Resveratrol-Eu-layered double hydroxide nanocomposite alleviates radiation-induced lung injury through antioxidant and IL-17/NF-κB-associated anti-inflammatory effects - Fangxiao Cao; Junzhe Yang; Xiaoyi Cai; Xin Zuo; Yiming Wang; Li Du; Yuxin Lu; Xiaochen Cheng; Tingting Liu; Shan Ma; Feiyu Zhao; Shanyue Guan; et al. (Chemical Engineering Journal, 2026)

Integrated physiological, transcriptomic and lipidomic analyses reveal the role of trans-2-octenal in the postharvest preservation of fresh walnut kernels - Jiamei Yuan; Yushan Du; Kun Zhang; Heyue Yang; Guangjin Li; Fengjun Wang (Postharvest Biology and Technology, 2026)

Efficacy and possible mechanism of trans-2-octenal in controlling grey mould caused by Botrytis cinerea on harvested fruit - Jiamei Yuan; Jie Yang; Yushan Du; Liwenqian Wang; Fengjun Wang; Guangjin Li (Postharvest Biology and Technology, 2026)

Amplified radiative effects of coated black carbon aerosols over the Tibetan Plateau - Jie Sun; Gang Zhao; Jinyuan Yu; Weili Lin; Yi Chen; Chunxiang Ye; Wenxu Fang; Wenhao Zhou; Baifeng Zhu; Jiawei Yang; Zhijun Wu; Tong Liu; et al. (Atmospheric Research, 2026)

Preparation of mesoporous polydopamine/thyme essential oil/fish scale gelatin photothermal antibacterial film and its application on cherry tomato preservation - Yunfeng Yang; Quanwen Liu; Peng Yang; Xiulian Li; Xiangquan Zeng; Fengjun Guo; Xinguang Fan (Food Chemistry, 2026)

Development and characterization of a walnut protein hydrolysate-Fe-vitamin C complex: Enhancing iron bioavailability through phytase-assisted modification - Sibao Zhao; Wenzhen Qiu; Yang Sun; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Electrochemical nitrite sensing using mass transfer signal with a catalyst-free small-sized rotating disk electrode for wastewater monitoring - Fengjun Yin; Xiaohui Yang; Shun Lu; Hanlin Zhang; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Zhaoming Chen; Hong Liu (Water Research, 2025)

Modeling electron competition and pH factor interactions improve cognitions of nitrite accumulation during denitrification - Xuehai Yue; Fengjun Yin; Hao Tan; Junxi Liu; Lin Chang; Xiaohui Yang; Sha Wang; Ying Zhao; Haofei Shi; Wei Zhang; Hong Liu (Environmental Research, 2025)

Efficient Zn2+ transport tailoring by BiOIO3 nanosheets modified glass fiber separator toward ultra-stable Zn metal anodes - Zijun Feng; Yongle Liang; Fengjun Niu; Yu Liu; Qiying Zhang; Guobao Xu; Xiaolin Wei; Liwen Yang (Chemical Engineering Journal, 2025)

Biochar promotes the dissolution of inorganic inactive phosphorus by mediating the bacterial community during corn stover and cattle manure composting - Linqin Zhao; Ying Li; Bowen Fan; Mengmeng Wang; Ning Sun; Fengjun Yang (Chemosphere, 2025)

A ternary composite with TeO2/Te heterostructure towards reversible six-electron transfer for advanced aqueous zinc batteries - Hengyu Yang; Xuefang Zhang; Yongle Liang; Fengjun Niu; Yu Ai; Guobao Xu; Xiaolin Wei; Liwen Yang (Chemical Engineering Journal, 2025)

All-Round stannic iodide as electrolyte additive Enables high-capacity and Long-Life aqueous zinc ion batteries - Huaijun Zhang; Hengyu Yang; Yu Ai; Xuefang Zhang; Yongle Liang; Fengjun Niu; Guobao Xu; Xiaolin Wei; Liwen Yang (Chemical Engineering Journal, 2025)

The preparation of fish scale gelatin-polydopamine photothermal sterilization film and its application for storage of cherry tomato - Yunfeng Yang; Xiulian Li; Ting Zhang; Xiangquan Zeng; Fengjun Guo; Quanwen Liu; Xinguang Fan; Da-Peng Yang (Food Packaging and Shelf Life, 2024)

Liquid-liquid addition reaction of ethylene oxide with hydrazine hydrate in microreactors: Kinetics and process optimization - Haiyun Ma; Lixia Yang; Chaoqun Yao; Shuainan Zhao; Fengjun Jiao; Guangsheng Luo; Guangwen Chen (Chemical Engineering Journal, 2024)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

HCMV IE1/IE1mut Therapeutic Vaccine Induces Tumor Regression via Intratumoral Tertiary Lymphoid Structure Formation and Peripheral Immunity Activation in Glioblastoma Multiforme - Xiaoli Yang; Shasha Jiang; Fengjun Liu; Zonghui Li; Wenxuan Liu; Xianjuan Zhang; Fulong Nan; Jun Li; Meng Yu; Yunyang Wang; Bin Wang (Molecular Neurobiology, 2024)
Glioblastoma multiforme (GBM), a highly malignant invasive brain tumor, is associated with poor prognosis and survival and lacks an effective cure. High expression of the human cytomegalovirus (HCMV) immediate early protein 1 (IE1) in GBM tissues is strongly associated with their malignant progression, presenting a novel target for therapeutic strategies. Here, the bioluminescence imaging technology revealed remarkable tumor shrinkage and improved survival rates in a mouse glioma model treated with HCMV IE1/IE1mut vaccine. In addition, immunofluorescence data demonstrated that the treated group exhibited significantly more and larger tertiary lymphoid structures (TLSs) than the untreated group. The presence of TLS was associated with enhanced T cell infiltration, and a large number of proliferating T cells were found in the treated group. Furthermore, the flow cytometry results showed that in the treatment group, cytotoxic T lymphocytes exhibited partial polarization toward effector memory T cells and were activated to play a lethal role in the peripheral immunological organs. Furthermore, a substantial proportion of B cells in the draining lymph nodes expressed CD40 and CD86. Surprisingly, quantitative polymerase chain reaction indicated that a high expression of cytokines, including chemokines in brain tumors and immune tissues, induced the differentiation, development, and chemokine migration of immune cells in the treated group. Our study data demonstrate that IE1 or IE1mut vaccination has a favorable effect in glioma mice models. This study holds substantial implications for identifying new and effective therapeutic targets within GBM.

Long-term nitrogen fertilization enhances crop yield potential in no-tillage systems through enhancing soil fertility - Shengping Li; Xueping Wu; Xiaojun Song; Xiaotong Liu; Huizhou Gao; Guopeng Liang; Mengni Zhang; Fengjun Zheng; Peng Yang (Resources, Conservation and Recycling, 2024)

Fast circulatory nitrification/denitrification process using continuous flow synchronous settling reactors promotes organic utilization efficiency in nitrogen removal - Fengjun Yin; Haotian Wei; Xuehai Yue; Hao Tan; Xiaohui Yang; Shun Lu; Sha Wang; Ying Zhao; Hong Liu (Chemical Engineering Journal, 2024)

Core microbes identification and synthetic microbiota construction for the production of Xiaoqu light-aroma Baijiu - Huan Wang; Yumei Wang; Yulei Ruan; Dan Ma; Han Wang; Shengzhi Yang; Linjie Lyu; Fengjun Yang; Xiaole Wu; Yefu Chen (Food Research International, 2024)

Biochar application can enhance phosphorus solubilization by strengthening redox properties of humic reducing microorganisms during composting - Bowen Fan; Changjiang Zhao; Liqin Zhao; Mengmeng Wang; Ning Sun; Zoutong Li; Fengjun Yang (Bioresource Technology, 2024)

Single-Cell RNA Sequencing Transcriptomics Revealed HCMV IE2-Related Microglia Responses in Alzheimer’s-Like Disease in Transgenic Mice - Fengjun Liu; Zhifei Wang; Delei Niu; Xianjuan Zhang; Fulong Nan; Shasha Jiang; Jun Li; Meng Yu; Xiaoli Yang; Shuyun Zhang; Xiaoqiong Zhou; Hui Wang; et al. (Molecular Neurobiology, 2024)
Although multiple factors are known to concur with Alzheimer’s disease (AD), the relationship between human cytomegalovirus (HCMV) and AD-like disease is unclear. Here, we propose a hypothesis that HCMV immediate-early 2 (IE2) protein promotes microglia activation and thus leads to AD-like disease. We successfully constructed IE2 transgenic mice expressing IE2 in the hippocampus. Single-cell sequencing analysis revealed that IE2 promoted the activation of microglia and upregulated the expression of disease-associated microglia genes. Differentially expressed gene analysis and pathway enrichment revealed that IE2 upregulated immune and nervous system disease-related genes. Immunohistochemical analysis showed that the expressions of both amyloid precursor protein (APP) and p-Tau were significantly upregulated in the brains of IE2 mice and were markers of AD. Taken together, these findings provide useful insights into AD-like disease activated by HCMV IE2.

Holocene aeolian activity triggered by climate change and endorheic-exorheic drainage transition in the Headwater Region of the Yellow River, Tibetan Plateau - Guangyin Hu; Jingjing Hu; Lupeng Yu; Linhai Yang; Xiangjun Liu; Fengjun Xiao; Zhibao Dong (Geomorphology, 2023)

Adaptive Graph-Learning Convolutional Network for Multi-Node Offshore Wind Speed Forecasting - Jingjing Liu; Xinli Yang; Denghui Zhang; Ping Xu; Zhuolin Li; Fengjun Hu (Journal of Marine Science and Engineering, 2023)
Multi-node wind speed forecasting is greatly important for offshore wind power. It is a challenging task due to unknown complex spatial dependencies. Recently, graph neural networks (GNN) have been applied to wind forecasting because of their capability in modeling dependencies. However, existing methods usually require a pre-defined graph structure, which is not optimal for the downstream task and limits the application scope of GNN. In this paper, we propose adaptive graph-learning convolutional networks (AGLCN) that can automatically infer hidden associations among multi-nodes through a graph-learning module. It simultaneously integrates the temporal and graph convolutional modules to capture temporal and spatial features in the data. Experiments are conducted on real-world multi-node wind speed data from the China Sea. The results show that our model achieves state-of-the-art results in all multi-scale wind speed predictions. Moreover, the learned graph can reveal spatial correlations from a data-driven perspective.

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Improving yield and nitrogen use efficiency of hybrid indica rice through optimizing nitrogen application strategies in the rice season under different rotation patterns - YongJian Sun; Dan Lin; YuanYuan Sun; FengJun Yan; Peng Ma; ChangChun Guo; FeiJie Li; ZhiYuan Yang; FuXian Xu; Jun Ma (Paddy and Water Environment, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

The amendment of Organic matters enhances the anaerobic dechlorination of Polychlorinated Biphenyls in Paddy Soil - Jingwen Chen; Fengjun Xu; Kai Yang; Chen Chen; Jixing Wan; Chaofeng Shen (Bulletin of Environmental Contamination and Toxicology, 2022)

Differences in Rice Productivity and Growth Attributes Under Different Paddy-Upland Cropping Systems - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Wanjun Ren (International Journal of Plant Production, 2022)

Removal of Hg2+ from desulfurization wastewater by tannin-immobilized graphene oxide - Heng Chen; Fengjun Liu; Chenjian Cai; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Characterization of microsatellites in the endangered snow leopard based on the chromosome-level genome - Chuang Zhou; Fengjun Li; Qinchao Wen; Megan Price; Nan Yang; Bisong Yue (Mammal Research, 2021)

Residual nitrogen from preceding garlic crops is important for double-cropped rice - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Nkrumah Malik; Wanjun Ren (Nutrient Cycling in Agroecosystems, 2020)

The effect of straw mulch on nitrogen, phosphorus and potassium uptake and use in hybrid rice - Fengjun Yan; Yongjian Sun; Xu Hui; Mingjin Jiang; Kaihong Xiang; Yunxia Wu; Qiao Zhang; Yuan Tang; Zhiyuan Yang; Yuanyuan Sun; Ma Jun (Paddy and Water Environment, 2019)

Complete mitochondrial genome of the Himalayan Monal Lophophorus impejanus (Phasianidae), with phylogenetic implication - Yang Chen; Fengjun Li; Qi Zhang; Qiong Wang (Conservation Genetics Resources, 2018)

Development history and accessibility evolution of land transportation network in Beijing-Tianjin-Hebei region over the past century - Yu Chen; Fengjun Jin; Yuqi Lu; Zhuo Chen; Yu Yang (Journal of Geographical Sciences, 2018)

Novel deletion of SLC34A2 in Chinese patients of PAM shares mutation hot spot with fusion gene SLC34A2–ROS1 in lung cancer - Shang Dandan; Chen Yuqin; Lu Wei; Peng Ziheng; Zhou Dapeng; Yang Jianzhu; Xin Xin; Liu Yonghong; Tian Fengjun (Journal of Genetics, 2018)

Effects of wheat straw mulch application and nitrogen management on rice root growth, dry matter accumulation and rice quality in soils of different fertility - Fengjun Yan; Yongjian Sun; Hui Xu; Yaozhu Yin; Haiyue Wang; Chunyu Wang; Changchun Guo; Zhiyuan Yang; Yuanyuan Sun; Jun Ma (Paddy and Water Environment, 2018)

Evolution and geographic effects of high-speed rail in East Asia: An accessibility approach - Fengjun Jin; Jingjuan Jiao; Yuanjing Qi; Yu Yang (Journal of Geographical Sciences, 2017)

Quantitative analysis of vascular parameters for micro-CT imaging of vascular networks with multi-resolution - Fengjun Zhao; Jimin Liang; Xueli Chen; Junting Liu; Dongmei Chen; Xiang Yang; Jie Tian (Medical & Biological Engineering & Computing, 2016)

CRP Acts as a Transcriptional Repressor of the YPO1635-phoPQ-YPO1632 Operon in Yersinia pestis - Yiquan Zhang; Fengjun Sun; Huiying Yang; Lei Liu; Bin Ni; Xinxiang Huang; Ruifu Yang; Dongsheng Zhou (Current Microbiology, 2015)

The Role of F-Fluorodeoxyglucose (FDG) Positron Emission Tomography–Computed Tomography (PET/CT) in the Screening of Cervical Cancer: A Literature Review - Fengjun Guo; Ruiqi Yang; Jingyan Tian; Limei Fan (Cell Biochemistry and Biophysics, 2014)

China’s economic development stage and its spatio-temporal evolution: A prefectural-level analysis - Yuanjing Qi; Yu Yang; Fengjun Jin (Journal of Geographical Sciences, 2013)

Sustainable development of the seriously polluted cities in China - Fengjun Cui; Xinjun Yang (Chinese Geographical Science, 1998)